Interpersonal Communication in Interpersonal Relationship between Single Mother and Children - Ivana, Raissa (Jurnal Komunikasi dan Bisnis, 2024)
The role of a single mother is very important in the lives of children, especially in building relationships with one another. One way to build this relationship in this context is to communicate effectively between single mother and children, especially by using two roles. To see the quality of a relationship. This can be seen from the quality of the communication itself. In this study, researchers used several conceptual and theoretical studies for research. The concepts used by researchers include the concept of interpersonal communication, the concept of interpersonal interaction, the interpersonal relationship value concept, the stages of interpersonal relations concept, the concept of interpersonal relations, and the theory used in this research is role theory according to Biddle and Thomas. This research was conducted using a qualitative descriptive approach. The data collection technique used the in-depth interview method, while the data collection used the observation and documentation method. Then the data would be analyzed using Miles and Huberman analysis. The conclusion of this research is from the five informants can be said that three informants have good interpersonal relations with communication that runs effectively even though there are those who need a process, but the progress is very visible. Two other informants, have poor interpersonal relations with ineffective communication and there is no balance reciprocity. The process of forming a relationship depends on interpersonal communication in every aspect, which is also influential in maintaining a relationship.